2015
DOI: 10.1007/s11695-015-1690-y
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in the Immediate Postoperative Phase in Patients Undergoing Roux-en-Y Gastric Bypass—a Randomized Controlled Trial

Abstract: Goals set for steps taken per day increase the amount of steps walked in patients undergoing gastric bypass surgery. Step counters and predefined goals can be used to facilitate mobilization after obesity surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…Some earlier research has been carried out with accelerometers in perioperative care, but these studies have focused on a relatively short postoperative period or used the accelerometer as an intervention to stimulate physical activities [1820]. Therefore, data representing the normal recovery process measured with an accelerometer are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Some earlier research has been carried out with accelerometers in perioperative care, but these studies have focused on a relatively short postoperative period or used the accelerometer as an intervention to stimulate physical activities [1820]. Therefore, data representing the normal recovery process measured with an accelerometer are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The question remains whether specific strategies (e.g., accompanied walks or supervised exercise) benefit patients receiving minimally invasive colorectal surgery. Wiklund et al observed that goals for steps did not significantly improve bowel function recovery or shorten LOS in patients undergoing gastric-bypass surgery (20). Staff-assisted facilitation of early mobilization also did not improve outcomes compared with traditional ERAS care for colorectal surgery (21).…”
Section: Discussionmentioning
confidence: 99%
“…The question remains whether specific strategies (e.g., accompanied walks or supervised exercise) benefit patients receiving minimally invasive colorectal surgery. Wiklund et al observed that goals for steps did not significantly improve bowel function recovery or shorten LOS in patients undergoing gastric-bypass surgery (16). Staff-assisted facilitation of early mobilization also did not improve outcomes compared with traditional ERAS care for colorectal surgery (17).…”
Section: Discussionmentioning
confidence: 99%